Tastes and Technology in a Two-Country Model of the Business Cycle: Explaining International Comovements - Stockman, Alan C.; Tesar, Linda L. (American Economic Review, 1995)
Trade on international financial markets allows people to insure country-specific risk and smooth consumption intertemporally. Equilibrium models of business cycles with trade on global financial markets typically yield international consumption correlations near 1 and excessive volatility of investment. We incorporate nontraded goods in the model and find that the implications for aggregate consumption, investment, and the trade balance are consistent with business-cycle properties of industrialized countries. However, the model driven by technology shocks alone yields counterfactual implications for comovements between consumption and prices at the sectoral level. Taste shocks produce price–quantity relationships more consistent with the data.